Analisis Pengaruh Struktur Modal Dan Struktur Kepemilikan Terhadap Kinerja Perusahaan - Dellia Santi Noviastuti; Ika Sasti Ferina; Rini Yayuk Priyati (Universitas Muhammadiyah Malang, 2022)
This study extends examining the effect of capital structure (Debt Equity Ratio) on firm performance (Tobin’s q dan ROA), quadratic (concave) effect of capital structure on firm performance, the effect of Multiple Large Shareholder Structure (MLSS) and institutional ownership on firm performance. This study differ from previous studies by pinpointing the category of debt to calculate Debt to Equity Ratio. The sample of this study is 424 observations from 53 non-financial companies listed on the Indonesia Stock Exchange including Index Kompas 100 from 2013 to 2020. Using fixed effect panel regression, this research finds inconsistent evidence that capital structure has insignificant negative effect on firm performance and has not a quadratic (concave) effect on firm performance. This study finds MLSS have insignificant negative effect on firm performance. This result could be caused by ownership structure in Indonesia is concentrated and percentage of MLSS is small. MLSS can not monitor the largest shareholder. This study also finds institutional ownership has insignificant negative effect on firm performance. This result could be caused by percentage of institusional owneship is small that can not monitoring manager behaviour in determining debt and dividen policy.